(untitled) (Journal of the Bangladesh Agricultural University, 2024)
The Barapukuria coal mining area in Dinajpur district of Bangladesh is vital for energy generation but raises significant concerns about its effects on the livelihoods and well-being of the local farmers. The study examined the socioeconomic impact of coal mine on farmers’ well-being. We collected primary data using a multistage random sampling technique through direct interviews during the paddy harvesting period from January to March 2020. Considering the scope of the study, farm-level cross-section data of a total of 100 rice-growing farmers from Parbatipur Upazila of Dinajpur district was collected for the present study. Descriptive statistics were used to depict the socioeconomic status of the farmers and the well-being of the farmers in the permitted coal mining areas was assessed using multiple linear regression analysis, taking social, economic, and environmental factors into account. The survey revealed that the majority of the respondents were male (96%) and were within the age range of 36-50 years, accounting for 52% of the total. About 52% of the farmers had a primary level education, whereas 37% of the farmers had agricultural experience ranging from 11 to 20 years. The study also found that environmental and economic factors of farmers’ well-being were affected significantly by the presence of coal mines. However, the effects of coal mines on social elements were determined to be insignificant. Considering the identified problems, it was recommended that farmers in these areas should be treated in a better way so that they do not have to change their profession. A variety of policies ought to be made accessible for the benefit of the farmers in the study area. J Bangladesh Agril Univ 22(4): 497–505, 2024